Dietary Behaviors among Patients with Type 2 Diabetes Mellitus in Indonesia - Aklima, Aklima; Kritpracha, Charuwan; Thaniwattananon, Ploenpit (Nurse Media Journal of Nursing, 2013)
Purpose: To describe the dietary behaviors among patients with Type 2 Diabetes Mellitus(T2DM) in Indonesia.Method: Sixty patients with T2DM who met the inclusion criteria were selected from fourvillages of the Banda Raya Community Health Centre in Banda Aceh, Indonesia. Patients’dietary behaviors were measured by the Self-Management Dietary Behaviors Questionnaire(SMDBQ). The SMDBQ was modified from the previous study with adequate reliability(Chronbach’s alpha was .82).Result: The subjects who participated in this study were middle aged adults (53 years). Morethan half of the subjects in this study were female (76.7%). All of the subjects were Muslim.More than one-third had an education level of senior high school (38.3%). The majority of thesubjects had no experiences with any previous educational program or counseling programrelated to dietary behaviors (86.7%). The results showed a moderate level of dietary behaviorsof patients with T2DM in Aceh, Indonesia.Conclusions: The dietary behaviors among Type 2 diabetic patients in Aceh, Indonesia wereat a moderate level. Regarding dietary behaviors scales, almost all items were at a moderatelevel. However, recognizing and consuming the amount of calorie needs was at a low level.Further research is needed in terms of dietary self-management by using an interventionapproach to improve the dietary behaviors of diabetic patients.Key words: Type 2 diabetes mellitus, dietary behaviors.